Asset Ownership and Contractability of Interaction - Andreas Roider (University of Bonn, Bonn Graduate School of Economics (BGSE), 2002)
In a property-rights framework, I study how organizational form and quantity contracts interact in generating investment incentives. The model nests standard property-rights and hold-up models as special cases. I admit general message-dependent contracts, but provide conditions under which non-contingent contracts are optimal. First, I contribute to the foundation of the property-rights theory: I characterize under which circumstances its predictions are correct when trade is contractible. Second, I study how the optimal use of the incentive instruments depends on the environment. This is in the spirit of the multitasking literature. Finally, the model produces implications of the property-rights theory that are empirically testable.
Keywords: L22; D23; L14; D82; 330; Property Rights; Incomplete Contracts; Specific Investments; Eigentumsrechtstheorie; Lieferanten-Kunden-Beziehung; Vertragstheorie; Investition; Sunk Costs; Theorie